Public transport in a small island of a developing country - M. Shafi q-Ur Rahman (urbe. Revista Brasileira de Gestão Urbana, 2012)
This paper explores the existing forms of public t ransport system and their services as well as travel pattern of people in Siquijor Province, an island of the Philippines. Household questionnaire survey, interview ofthe passengers of various public transport m o des at their stations, anda detailed participatory observationwe re conducted for the research. Bus, jeepney3, easyride4, tricycle5, and habalhabal6 are the available publictransport systems in the island. However, these services do not provide travel time, waiting time, availabilityor frequency, comfort, and safety that is required by passenger s. Majority of the people mostly prefer the easyride for comfort and less waiting time whilst the bus for comfort. Considering the travel pattern, socioeconomicsituation and topographic condition, the research tri ed to identify which fo rm of public transport system would be appropriate for the island. lt was found that bus is appropriate for longer trips while easyride for the in ter-municipal trips and habalhabal for the trips in mountain are as.